2024
DOI: 10.1109/access.2024.3357091
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Undersampling and Oversampling for Handling Imbalanced Credit Card Data

Maram Alamri,
Mourad Ykhlef

Abstract: Recent developments in the use of credit cards for a range of daily life activities have increased credit card fraud and caused huge financial losses for individuals and financial institutions. Most credit card frauds are conducted online through illegal payment authorizations by data breaches, phishing, or scams. Many solutions have been suggested for this issue, but they all face the major challenge of building an effective detection model using highly imbalanced class data. Most sampling techniques used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The Tomek links undersampling (TLUS) method is used to balance imbalanced datasets by removing observations located between two different classes. The basic idea behind Tomek links is to identify pairs of observations, one from the majority class and one from the minority class, that are closest to each other but belong to different classes (Alamri & Ykhlef, 2024;Devi et al, 2017). These pairs are called Tomek links (Devi et al, 2017, p. 3).…”
Section: Tomek Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tomek links undersampling (TLUS) method is used to balance imbalanced datasets by removing observations located between two different classes. The basic idea behind Tomek links is to identify pairs of observations, one from the majority class and one from the minority class, that are closest to each other but belong to different classes (Alamri & Ykhlef, 2024;Devi et al, 2017). These pairs are called Tomek links (Devi et al, 2017, p. 3).…”
Section: Tomek Linksmentioning
confidence: 99%
“…While TomekLinks undersampling resulted in higher overall accuracy compared to RUS and CNN undersampling techniques, the latter two tend to have more consistent and moderate precision and recall scores. These ndings indicate that RUS and CNN may provide a more balanced trade-off between precision, recall, and accuracy, whereas TomekLinks may prioritize accuracy at the expense of precision and recall(Alamri & Ykhlef, 2024;Devi et al, 2017). Furthermore, the fact that precision and recall scores are consistent across different algorithms suggests that RUS and CNN may be able to perform better in a variety of situations compared to TomekLinks.In terms of the AUC, TomekLinks undersampling demonstrated reasonable performance overall, albeit slightly less effective than NearMiss.…”
mentioning
confidence: 96%
“…Each of these approaches aims to mitigate the skewness inherent in imbalanced datasets, enhancing the model's ability to accurately identify and classify minority-class instances. Hence, the former involves resampling the training data to balance classes (e.g., undersampling, oversampling, or hybrid methods) [9][10][11][12][13], while the latter involves altering the classifier's learning process, known as algorithmic modifications (e.g., cost-sensitive learning, thresholding, or ensemble methods) [14,15]. Haixiang et al have demonstrated that in the domain of medical datasets, re-sampling-based ensemble classifiers are extensively utilized to tackle imbalances [4].…”
Section: Introductionmentioning
confidence: 99%